The Iconography of Saint Dominic: The Person, the Image and the Problem of Expressing Holiness - Valečkaitė, Birutė (Religija ir kultūra, 2015)
[full article and abstract in Lithuanian; abstract in English] In this article, the issue of the “disappearing” personality of St. Dominic (1170–1221) is analyzed through showing the main aspects of his portrayal and the expression of his holiness in biographical and iconographic sources. In these texts, he is called “holy” with a reference to a conscious imitation of Jesus Christ. In the iconography, the signs of his sanctity became the only signs of his personality, and his figure is used as an example of the adoration of God. If losing a vivid personality is connected with expressing holiness, this problem refers to a concept of the icon formulated by Jean-Luc Marion. It gives us an opportunity to call St. Dominic a typical icon, transferring the adoration and losing his own originality. The 13th century concept of sanctity, expressed in the texts of St. Thomas Aquinas, enables us to understand St. Dominic’s image as a continuation of the saint’s choice to become a reference to God.